The Effect of The Taxation System and Tax Justice on The Succes of The Tax Amnesty at KPP Pratama Makassar Utara - Liong, Harlina; Uluputty, Nurdjanna Fadjrin; Daing, Ardaningsi (Universitas Negeri Makassar, 2023)
This research aims to determine the effect of the taxation system and justice on the success of the tax amnesty KPP Pratama Makassar Utara. Where in this research using a quantitative approach. The object of this research is the employees at KPP Pratama Makassar Utara. This research uses nonprobability with sample selection done using the Slovin formula and obtained a sample of 52 people. Collection data using the documentation method and questionnaires distributed to respondents and processed using SPSS version 23. The analysis design data used was multiple linear regression. The results of this research indicate that the results of partial hypothesis testing that the taxation system has no significant effect on the success of the tax amnesty, and so tax justice has a significant effect on the success of the tax amnesty. Meanwhile, the simultaneous test shows that the taxation system and tax justice have a simultan and significant effect on the success of the tax amnesty.